1993
DOI: 10.5006/1.3316126
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Homogenization and Artificial Aging Heat Treatments on Corrosion Behavior of Mg-Al Alloys

Abstract: The influence of heat treatment on corrosion behavior of magnesium-aluminum (Mg-9Al) alloys was investigated by studying the electrochemical properties of Mg-9Al in the solution-treated (T4) and artificially aged (T6) conditions. The alloys' properties were compared to those of pure Mg, the intermetallic Mg 17 Al 12 phase, and different Mg-Al-based alloys (Mg-3Al, AZ91). The Mg-9Al alloy exhibited better corrosion resistance in the T6 condition than in the T4 condition because of the intermetallic Mg 17 Al 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 3 publications
1
46
0
Order By: Relevance
“…Aging treatments are widely used for structural materials such as ferrous alloys, Al and Mg alloys, in order to tailor their microstructure to achieve the desired mechanical (and sometimes corrosion) properties. 71,72 Several researchers have explored the effect of aging on the corrosion behaviour of CCAs. 60,73 For the Cu 0.5 CoCrFeNi alloy, 60 it has been shown that aging at higher temperatures (1250 and 1350°C) for 24 h improved the corrosion resistance of the alloy in 0.6 M NaCl, compared to aging at lower temperatures (350-1100°C).…”
Section: The Influence Of Processing Methods On the Corrosion Of Ccasmentioning
confidence: 99%
“…Aging treatments are widely used for structural materials such as ferrous alloys, Al and Mg alloys, in order to tailor their microstructure to achieve the desired mechanical (and sometimes corrosion) properties. 71,72 Several researchers have explored the effect of aging on the corrosion behaviour of CCAs. 60,73 For the Cu 0.5 CoCrFeNi alloy, 60 it has been shown that aging at higher temperatures (1250 and 1350°C) for 24 h improved the corrosion resistance of the alloy in 0.6 M NaCl, compared to aging at lower temperatures (350-1100°C).…”
Section: The Influence Of Processing Methods On the Corrosion Of Ccasmentioning
confidence: 99%
“…He also reported that galvanic corrosion can be accelerated with an increase in the ratio of cathode (¢ phase) to anode (Al-rich ¡ phase). On the other hand, as described above, other researchers 8,21,22) reported that finely and homogenously distributed ¢ phases in as-cast and aged AZ91 alloys act as a barrier against corrosion of the ¡ phase. In general, during solidification of AZ91 alloys, the aluminum solute is ejected into the liquid phase, leading to continual enrichment of the liquid and lower solute concentrations in the primary ¡ phase.…”
Section: Resultsmentioning
confidence: 94%
“…One researcher 18) reported that a higher corrosion rate was obtained in a T6-treated cast AZ91 alloy as compared with a solution-treated cast AZ91 alloy. On the other hand, other researchers 14,21,22) reported that the T6-treated AZ91 cast alloy exhibited a lower corrosion rate than the solution-treated AZ91 cast alloy because finely and homogenously distributed ¢ phases act as a barrier against the development of corrosion of the ¡ phase. The current experimental results seem to demonstrate a tendency toward the latter results.…”
Section: Resultsmentioning
confidence: 98%
“…Oxygen usually does not appear to play a major role on Mg corrosion according to some ref. 8,12). The cathodic scans in a NaCl solution saturated with Mg(OH) 2 were unchanged by nitrogen deaeration of the electrolyte.…”
Section: Introductionmentioning
confidence: 88%
“…The cathodic scans in a NaCl solution saturated with Mg(OH) 2 were unchanged by nitrogen deaeration of the electrolyte. 12) However, in Baril 8) and Brun's 13) work, the current densities were lower and the corrosion resistance was higher in deaerated corrosive condition.…”
Section: Introductionmentioning
confidence: 99%